2023
DOI: 10.1088/1361-6595/acda5c
|View full text |Cite
|
Sign up to set email alerts
|

Electron impact cross-sections and rate coefficients of Si+2 ions relevant to collisional radiative modeling of silicon plasma

Abstract: We report the fine structure resolved electron impact excitation cross-sections of Si+2 from its ground state 3s2 (J = 0) to the 41 excited fine structure levels of the configurations 3s3p, 3p2, 3s3d, 3s4s, 3s4p, 3s5s, 3s4d, 3s4f, 3s5p, 3s5d and 3s5f using relativistic distorted wave theory. The excitation cross-sections from excited metastable levels (3P0,3P2) of the configuration 3s3p to higher excited levels as well as for some other dominant transitions relevant to plasma modeling are also obtained. In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 39 publications
3
1
0
Order By: Relevance
“…In contrast, for the J = 0 → 1 transition, the final level has an even parity with an odd angular momentum, causing the direct T-matrix term to be zero. A similar trend is also observed in the recent studies by Umer et al [29] and Baghel et al [30]. Umer et al [29] reported the relativistic convergent close coupling (RCCC) calculations for the cross sections of the excitation from 5s 2 → 5s6s for Sn 2+ .…”
Section: Figures 2(a)-(d)supporting
confidence: 83%
See 3 more Smart Citations
“…In contrast, for the J = 0 → 1 transition, the final level has an even parity with an odd angular momentum, causing the direct T-matrix term to be zero. A similar trend is also observed in the recent studies by Umer et al [29] and Baghel et al [30]. Umer et al [29] reported the relativistic convergent close coupling (RCCC) calculations for the cross sections of the excitation from 5s 2 → 5s6s for Sn 2+ .…”
Section: Figures 2(a)-(d)supporting
confidence: 83%
“…Consequently, the direct T-matrix element for this transition vanishes, in contrast to the other transitions (with even J f and even parity), resulting in a more rapid decrease in the cross section as the incident electron energy increases. A similar behavior is also observed in the RCCC calculations of the excitation cross sections for 5s 2 → 5p 2 for Sn 2+ of Umer et al [29], and the RDW calculations of excitation cross sections for 3s 2 → 3p 2 for Si 2+ of Baghel et al [30].…”
Section: Figures 2(a)-(d)supporting
confidence: 78%
See 2 more Smart Citations